Penerapan metode Isothermal Remanent Magnetization (IRM) untuk menentukan jenis mineral magnetik pada lindi di tempat pembuangan akhir (TPA) Air Dingin Kota Padang (Application of the Isothermal Remanent Magnetization (IRM) method to determine the type of magnetic minerals in leachate at the Air Dingin Landfill Padang City) - Mulyandri Putra; - Mahrizal; Fatni Mufit (Department of Physics – Universitas Negeri Padang UNP, 2015)
Padang city waste removed and processed in Air Dingin Landfill, Balai Gadang Village, Kecamatan Koto Tangah. On the location of the Landfill there were rivers used by residents for daily needs. Leachate generated from Landfill cast into the river can contaminate the River, which that cause the river’s water black and smelling. This research aims to determine the type of magnetic minerals in Leachate in the Air Dingin Landfill city of Padang, as an indicator of water pollution by leachate. This research uses the 6 samples taken from samples of the sediment pond, sediment River and sediment sewers on Air Dingin Landfill. Instruments used for sampling is Ekmam Grab. Types of magnetic mineral samples are specified by giving a magnetic field toward the sample using the method of Isothermal Remanent Magnetization (IRM) with instruments Electromagnetic Weiss. Data analysis was done with a given magnetic field of plotting for the intensity of magnetization of the sample which has reached saturation and compared to a standard curve of the IRM for viewing different types of magnetic mineral magnetite or hematite. The value of the magnetic field of the sample measured experiencing saturation at the time value is smaller than 300 mT. Saturation curve based on IRM mineral types in a sample of leachate, rivers and sewers Air Dingin Landfill city of Padang in the majority is the mineral magnetite (Fe3O4)